Technologies and crisis of democracy: challenges in practicing and teaching of journalism in Brazil - Amaral Filho, Nemézio (2019)
The purpose of this article is to briefly analyze the economic-ideo- logical model of the communication market in Brazil, highlighting its influ- ence on the current national political scene. Then we address the tensions caused by the flows, and not a particular element, of the new communication and information technologies in the crisis of the enunciative authority of jour- nalism; At the same time, we will reinforce the importance of this office for the maintenance of democracy in crisis in the country in particular, and in the West in general, through the mapping of technological strategies adopted by companies and professionals. Finally, in the light of similar research, we will conclude with the design of the curricular guidelines of what we understand should guide the debates on the transition of journalistic education (increas- ingly transdisciplinary, resorting to new technological support and the neces- sary reinforcement of humanistic strengthening) in the Brazilian universities. Later, suggestions are presented for the inclusion of media companies (large, medium, small and foreign on national soil), NGOs and civil society in the debate about journalism that we want in the midst of the democracy crisis.